2.80. Wyznacz pochodną funkcji: a) c) e) f(x) = (x ^ 3 – 2)/(3x ^ 2 + x) f(x) = (x ^ 2 + 8)/(x + 2) f(x) = (x ^ 4 + 3x + 2)/(x ^ 3 + 1) b) f(x) = 2sqrt(x) – 1/x d) f(x) = 2x ^ 4 – sqrt(x) + 5 D) f(x) = sqrt(7) + sqrt(x) b) f(x) = (2x ^ 2 – 3)(4x ^ 2 + 3x) d) f(x) = (2x ^ 4 + 4x ^ 2)(x ^ 3 + x + 3) f(x) = (x ^ 2 + x + 1/x)(sqrt(x) + x) f(x) = (- 2x)/(3x – 1) f(x) = (3x ^ 2 + 7x)/(6x + 1) f(x) = (2x)/(x ^ 2 – 5) b) d) f) f(x)=D f(x) = (4x ^ 2 – 5x)/(x ^ 2 + x + 2) b) d) f(x) = 5/(x ^ 4 + x ^ 3 + 1) n f(x) = x/(x ^ 5 – 1)

 2.80. Wyznacz pochodną funkcji: a) c) e) f(x) = (x ^ 3 – 2)/(3x ^ 2 + x) f(x) = (x ^ 2 + 8)/(x + 2) f(x) = (x ^ 4 + 3x + 2)/(x ^ 3 + 1) b) f(x) = 2sqrt(x) – 1/x d) f(x) = 2x ^ 4 – sqrt(x) + 5 D) f(x) = sqrt(7) + sqrt(x) b) f(x) = (2x ^ 2 – 3)(4x ^ 2 + 3x) d) f(x) = (2x ^ 4 + 4x ^ 2)(x ^ 3 + x + 3) f(x) = (x ^ 2 + x + 1/x)(sqrt(x) + x) f(x) = (- 2x)/(3x – 1) f(x) = (3x ^ 2 + 7x)/(6x + 1) f(x) = (2x)/(x ^ 2 – 5) b) d) f) f(x)=D f(x) = (4x ^ 2 – 5x)/(x ^ 2 + x + 2) b) d) f(x) = 5/(x ^ 4 + x ^ 3 + 1) n f(x) = x/(x ^ 5 – 1) 

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz